2 - Public Sector Reforms In Africa: A Philosophical Re-Thinking - Omoyefa, Paul Sunday (Africa Development, 2021)
Public sector reform (PSR) has been quite popular in African. However, the inadequate understanding of the philosophical basis of the reforms has led to many African countries to equating PSR with privatization and commercialization of public enterprises, downsizing of the public service workforce and the war on corruption. While many African countries are pursuing with the necessary vig- our these policies, which were induced by former colonial masters and so-called development agencies, there has been little or no success as compared with the pre-PSR era. The aim of this paper is to bring out, in clear terms, the fact that the present PSR cannot achieve success because of the threat of sustaining contin- ued control of the African economies and policies by the Breton Woods institu- tions, the sale of public enterprises to multinational companies, the migration of the best African brains to Europe and America, corruption and neo-colonialism. In essence, this paper advocates a philosophical re-thinking of PSR. This will start with reforming the minds of African leaders to reform the body politic. This study shows that PSR in Africa that fail to take note of the ethical and communal values and peculiar situations of various African countries will definitely fail.